TI_GERICHTE 12.2012.168 vom 13. Dezember 2012 , Tutela giurisdizionale dei casi manifesti, contratto di mutuo documentato - TI Tribunale d'appello (2012)
Tutela giurisdizionale dei casi manifesti, contratto di mutuo documentato